HETEROTOPIC OSSIFICATION - Burcu Yanık; Peyman Yalçın (Archives of Rheumatology, 2003)
Heterotophic ossification is a pathological new bone formation in the soft tissue. It generally occurs secondary to brain injury, spinal cord injury, cerebrovascular disease, bone fracture, dislocation and joint replacements. The diagnosis and the treatment of this complication in both neurological and orthopaedic rehabilitation are essential. Etiology, clinical features, diagnosis and the treatment of heterotopic ossification are discussed in this article.